The social impact of emotional tears - Vingerhoets, Ad J. J. M. (Motiv Emot, 2016)
The question what specific functions the production of emotional tears fulfills has received only limited attention of behavioral scientists. We report the results of two studies on the social impact of emotional tears. In Study 1 (96 Dutch females), perceived helplessness and felt connectedness predicted the willingness to help a person depicted as crying tearfully, while perceived friendliness did not. In Study 2 (US sample, 128 males, 68 females) all three of these variables mediated the effect the display of tears had on the willingness to help. Our results replicate and extend previous work and add to current knowledge by showing that tearful crying facilitates helping behavior and by identifying reasons why people are more willing to help criers. These findings help to put forth novel predictions on the impact of tearful crying on others.